Giblet Organs and Digestive Performance of Native Chickens in the Pullet Phase Fed Diets Supplemented with Propionic Acid - Agustina Viktoria Tae; Yuliana Naisali; Charles V. Lisnahan; Lukas Pardosi (Animal Science Study Program, Faculty of Agriculture, Science and Health, Universitas Timor, 2026)
The purpose of this study was to examine the effect of propionic acid levels in feed on the performance of giblet organs and digestive tracts of pullet-phase Native chickens. A total of 80 Native chickens aged 12 weeks with an average weight of 400 g were used in this study. The research design applied was a Completely Randomized Design (CRD). Chickens were randomly divided into four treatments with four replications, where each replication consisted of four Native chickens. The treatments given were T0: control feed without propionic acid; T1: control feed + 0.25% propionic acid; T2: control feed + 0.50% propionic acid; T3: control feed + 0.75% propionic acid. Data analysis was conducted using ANOVA, followed by the Duncan Test to determine differences between treatments. The results showed that live weight, giblet weight, pancreas weight, intestine weight, intestine length, proventriculus weight, were highest in the T3 control feed + 0.75% propionic acid treatment, respectively, at 1622.36±38.24 g/head; 59.23±0.39 g/head; 3.54±0.04 g/head; 27.24±0.57 g/head; 27.24±0.57 g/head; 129.33±0.68 cm/head; 6.04±0.18 g/head. The highest giblet percentage and proventriculus percentage were in the T0 control feed treatment without propionic acid at 3.74±0.12%/head and 0.38±0.01%/head, respectively. The highest percentage of pancreas weight was in the T2 treatment of control feed + 0.50% propionic acid and the T3 treatment of control feed + 0.75% propionic acid, which was 0.22 ± 0.01%/head. The highest percentage of intestine weight was obtained in the T2 treatment (control feed + 0.50% propionic acid) with a value of 1.71 ± 0.03%/head. Analysis of variance showed that the treatment significantly affected the live weight, giblet organ weight, pancreas weight, percentage of pancreas weight, small intestine weight, intestine length, and proventriculus weight of pullet phase Native chickens (P <0.05). It can be concluded that the addition of 0.75% propionic acid to the control feed had a positive effect on the performance of the giblet organ and digestive tract of Native chickens.